Design of timber-concrete composite floors - Luetje, George Andrew (My University, 2025)
Timber-concrete composite (TCC) floors use composite action to achieve higher strength and longer spans compared to timber structures. This report investigates the design and performance of TCC floors in accordance with published design guides and references. The design methods of the connections between timber and concrete are discussed. The report also compares the design of a typical bay using TCC, concrete, and timber structures. A comparative analysis is performed on the flexural strength, shear strength, deflection, total thickness, and material cost of the three. Results show that TCC floors can achieve similar strengths to the other floors while having a smaller thickness.
Keywords: Timber-concrete composites; CLT; Concrete